VARIABILITY IN THE ORAL CAVITY IN ENDOCRINE DISEASES - Kurbanov Bekhzod; Zoyirov Tulkin; Shukurova Nodira Tillayevna (Journal of new century innovations, 2024)
Annotation. One of the problems of modern clinical dentistry is the increase in inflammatory diseases of the oral cavity, occurring against the background of secondary immune deficiency [3,6,8]. An internal factor influencing the immune response is the endocrine system, which is part of the neurocrine perylation homeostasis complex. An important role in the etiopathogenesis of various dental diseases is played by the complex multifunctional relationships between the immune, nervous and endocrine systems. Endocrinological aspects of dental diseases are reflected in a number of fundamental scientific studies [4,5,9], which indicate a close relationship between diseases of the oral organ systems and endocrine pathology systems. One of the most common diseases of the endocrine system is hypothyroidism. A number of authors indicate a high prevalence of chronic generalized periodontitis with hypothyroidism [2,4,9]. Studies by a number of authors have revealed a high incidence of dental caries and a higher degree of increase in the intensity of caries in children living in areas of iodine deficiency. However, these data are small and scattered. A comprehensive and in-depth study of the effect of hypothyroidism on the development of oral diseases has not been conducted.